Understanding How Personal Networks Change: Wave 1 - Fischer, Claude S. ([Verlag nicht ermittelbar], 2018)
Understanding How Personal Networks Change: Wave 1 (UCNets) is the University of California Berkeley Social Networks Study, a longitudinal study with the objective of understanding how network composition changes over time as a result of life course transitions - e.g., graduation, marriage, retirement or widowhood - and how these changes are related to health status and outcomes. Using mostly addressed-based sampling from six San Francisco bay area counties, the study recruited participants in two age groups (cohorts) - 21-30 year-olds and 50-70 year-olds -- to maximize the possibility of experiencing a life transition. There are 3 waves of interviewing. Two have been completed (winter 2015-2016, and winter-spring 2017) and a third will commence in spring 2018. In Wave 1, the majority of respondents completed a face-to-face interview, with the rest filling out a comparable web survey. The survey contains items regarding households, personal networks, family milestones, employment, health status and behavior, personality and demographic characteristics.